Synergistic effect of graphene oxide and silver nanoparticles as biostimulant improves the postharvest life of cut flower bird of paradise (Strelitzia reginae L.) - Thakur, Meenakshi; Chandel, Anjali; Guleria, Shweta; Verma, Vipasha; Kumar, Raghawendra; Singh, Gurpreet; Rakwal, Anjali; Sharma, Diksha; Bhargava, Bhavya (Frontiers in Plant Science, 2022)
Bird of Paradise (Strelitzia reginae L.) is one of the important tropical cut flowers. Generally flower like bird of paradise (BOP) grown for commercial ornamental market must be of high pre and postharvest quality. Thus to improve the postharvest longevity and increased marketability, the relative efficacies of two different biologically synthesized nano-particles (NP) were evaluated. The novel proprietary stimulants were graphene oxide (GO), and silver nanoparticles (SNPs). The NPs treatments were applied as vase (lower concentrations) solutions. Among all the applied treatments, the synergistic effect of GO+SNPs at 1 µL L-1 vase solution significantly (p ≤ 0.05) prolong the post-harvest life of cut flowers of BOP. Increased vase life over the deionised water (DI) control was associated with better maintenance of relative water uptake, relative fresh weight, suppressed microbial density at stem-end and delay of stem blockage, reduced electrolyte leakage, malondialdehyde (MDA), SOD, and POD activity. In contrast to control, administration of NPs gave better results for all the analyzed parameters. Application of biologically synthesized NPs in combination (GO+SNPs at 1 µL L-1) extended the vase life of cut flowers by 6 days in comparison with control flowers, and overall, showed better results than the control. The findings of the studies revealed that the standardized NPs could have more potential in prolonging the postharvest life of cut flowers of BOP. Thus this technique can be used as a novel postharvest technology for commercial application in cut flowers.